Energy Audit of Flouresen Lights at School Building C III Floor Politeknik Negeri Semarang - Supriyo, Supriyo; Margana, Margana; W, Wiwik Purwati; Suwarti, Suwarti; Mulyono, Mulyono (Eksergi, 2022)
Energy audit is very necessary to calculate the level of energy consumption of a building or buildings. The research includes the amount of energy consumption based on the initial energy audit and detailed energy audit as well as saving opportunities based on conditions in the field. Based on the initial energy audit, the value of the Energy Consumption Intensity (IKE) is 0.699 kWH/m2month, while in the detailed audit the IKE value is 0.935 kWH/m2month. Based on the results of a detailed energy audit, the lighting measurement of 325 lux still meets the requirements for a classroom with a standard between 250 lux to 500 lux.